2014
DOI: 10.30955/gnj.001379
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rainfall and drought in Rajasthan state, India

Abstract: Rainfall indices and Standardized Precipitation Index (SPI) were obtained for Rajasthan State characterized as the most sensitive and vulnerable state in India. Daily rainfall data of 35 years for 31 well-spread stations were used to generate critical area maps. From the analysis of rainfall indices, it is observed that few stations situated in east and south-eastern side in the state have shown high negative change for annual and monthly rainfall but not such negative change is observed in the case of averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Interestingly, it is noteworthy here that the western region in the Marusthali desert area of the state, exhibits a concurrent rise in the annual average precipitation, which is also mentioned in study ofKumar et al (2010). Interestingly few stations of the eastern part of the state are showing the decreasing trend of the mean annual rainfall which is indistinguishable with the study ofMundetia and Sharma (2015);Mondal et al (2015);Kumar et al (2010). The study ofLal et al (2001) has also mentioned that the arid western part of the state soon coming could receive higher rainfall because of the warming climate.…”
supporting
confidence: 66%
“…Interestingly, it is noteworthy here that the western region in the Marusthali desert area of the state, exhibits a concurrent rise in the annual average precipitation, which is also mentioned in study ofKumar et al (2010). Interestingly few stations of the eastern part of the state are showing the decreasing trend of the mean annual rainfall which is indistinguishable with the study ofMundetia and Sharma (2015);Mondal et al (2015);Kumar et al (2010). The study ofLal et al (2001) has also mentioned that the arid western part of the state soon coming could receive higher rainfall because of the warming climate.…”
supporting
confidence: 66%
“…Increasing trends in precipitation during autumn and winter, whereas decreasing trends during monsoon and spring were reported by Pal and Al-Tabbaa (2011) based on the analysis for the period of 1954-2003. Many other studies were done by the authors in which rainfall pattern, distribution, frequency, etc. of different North Indian states were studied, that is, Haryana (Chauhan et al, 2022;Nain & Hooda, 2019), Himachal Pradesh (Jaswal et al, 2015), Punjab (Kaur et al, 2021), Rajasthan (Mundetia & Sharma, 2014;Pingale et al, 2013), Uttarakhand (Malik & Kumar, 2020) and Uttar Pradesh (Guhathakurta et al, 2020). Mondal et al (2022) showed that the extreme precipitation events across South Asia may increase up to 3.5%-6.6% due to increase in warming from 1.5 to 2.0°C.…”
mentioning
confidence: 99%